Prospects for laser based powder bed fusion in the manufacturing of metal electrodes: A review - Nyamekye Patricia; Nieminen Pinja; Bilesan Mohammad Reza; Repo Eveliina; Piili Heidi; Salminen Antti (Elsevier, 2022)
Additive manufacturing, (AM), includes seven subcategories that can directly manufacture components structures from a computer-designed model layer by layer. Laser-based powder bed fusion (L-PBF) is one of type of the subcategories of AM. L-PBF is a fast and cost-efficient production method that offers the advantages of being implementable with a diverse range of raw materials, possessing a high level of freedom in customization, and producing less waste. L-PBF can potentially enable the production of hierarchically complex shaped electrochemical separation units. This study examines the use of L-PBF for the fabrication of metal electrodes for electrochemical processes. The aim is to address a literature gap by presenting a state-of-the-art review of L-PBF electrodes used in electrochemical cells. The study investigates existing research on electrochemistry and identifies potential benefits from use of L-PBF metal electrodes. Electrochemical reactors in industry require electrodes with a large electrode/electrolyte interface that can hold electrolytes efficiently and reduce the diffusion path of electrons and ions on the active surface of electrode. Meeting these demands require electrodes with specific characteristics such as high surface area and improved mass transport. This review shows that L-PBF can manufacture optimized electrodes satisfying the requirements for electrochemical cells in industrial applications
(c) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license ( http://creativecommons.org/licenses/by/4.0/ )